Macroeconomic Determinants of Credit Risk in Poland, with Particular Concerning Exchange Rates - Pluskota, Anna (Journal of Finance and Financial Law, 2021)
The purpose of the article. The aim of the study is to show the impact of the key macroeconomic determinants of the credit risk of the banking sector in Poland in 2011–2020. This aim was achieved by analysis of the Pearson correlation coefficient and econometric models allowing to determine the impact of individual variables on the NPL index.Methodology: The empirical part includes the presentation and description of basic descriptive statistics, as well as the calculation of the Pearson correlation coefficient with the interpretation of the obtained results. The dynamic econometric model describing the variability of the NPL ratio was built using mainly macroeconomic variables.Results of the research: Research has shown the impact of changes in the unemployment rate and the inflation rate on credit risk. On the other hand, the impact of economic growth on the NPL ratio in the analyzed period was not statistically significant. The relationship between credit risk and changes in foreign exchange rates (CHF, USD, EUR) turned out to be negative in the analyzed period, which means that the increases in exchange rates of these currencies did not result in a significant burden of credit risk in the banking sector in Poland.